Biodiversity in tropical rainforests: Calleida Dejean, 1825 at the BIOLAT Biological Station, Rio Manu, Peru, with descriptions of seven new species (ColeopteraCarabidae, Lebiini). Part 1 - Casale, Achille (Zookeys, 2021)
A monographic contribution is presented on the species of the genus Calleida Dejean, 1825 at the BIOLAT Biological Station, Rio Manu, Pakitza, Peru, sampled by Terry Erwin and his co-workers. The following seven new species are described: C. solitariasp. nov., C. manuensissp. nov., C. anomalasp. nov., C. demathanisp. nov. (type locality: Peru, Tarapoto, but sampled also at Rio Manu), C. erwinisp. nov., C. marginithoraxsp. nov., and C. maximasp. nov. Relationships of each species are discussed, and a preliminary survey is presented of the genus Calleida in Peru.